EСОNOMIC ACTIVITY AS A FACTOR IN HUMAN DEVELOPMENT - Балюк, О. О. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2013)
The paper analyzes the main coming concept – the concept of ―economy‖, compares the various meanings, which have been studied in the literature. The questions of decent solving problems of human development are considered. Such a development is possible only through collaboration, partnership, where the relationship of interaction, cooperation between different subjects profess in key of value – rational approach to economic phenomena. The process of humanization, value competitiveness and motives of the person as a holistic being have the highest priority in this case.